2014
DOI: 10.1177/1098612x14539499
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials involving cats

Abstract: Clinical trials are frequently hindered by difficulty recruiting eligible participants, increasing the timeline and limiting generalizability of results. In veterinary medicine, where proxy enrollment is required, no studies have detailed what factors influence owner participation in studies involving cats. We aimed to investigate these factors through a survey of owners at first opinion practices. The survey was designed using feedback from a pilot study and input from clinical researchers. Owners were asked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The variable that received the highest importance rating in the VIN survey was having a pet with a condition that could benefit from the trial, reported by 71% of respondents. This finding was similar to that in a study 14 of cat owners’ views on clinical trial participation, in which 73% of respondents gave this item the highest importance rating (5-point scale). Veterinarian endorsement of the trial was also rated as important, although only 33% of VIN survey respondents and 26% of VP survey respondents gave this the highest importance rating.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The variable that received the highest importance rating in the VIN survey was having a pet with a condition that could benefit from the trial, reported by 71% of respondents. This finding was similar to that in a study 14 of cat owners’ views on clinical trial participation, in which 73% of respondents gave this item the highest importance rating (5-point scale). Veterinarian endorsement of the trial was also rated as important, although only 33% of VIN survey respondents and 26% of VP survey respondents gave this the highest importance rating.…”
Section: Discussionsupporting
confidence: 88%
“…Veterinarian endorsement of the trial was also rated as important, although only 33% of VIN survey respondents and 26% of VP survey respondents gave this the highest importance rating. This finding was likely an underestimation, given that physician recommendation has been cited as a critical feature of clinical trial participation in human medicine, 11 and in the study 14 of cat owners, 56% assigned the highest importance rating (5-point scale) to the item “My veterinarian recommended the trial.” Additional research would be useful to compare attitudes of pet owners (including dog owners) with attitudes of small animal practitioners to identify commonalities (and gaps) between importance ratings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the specific situation of clinical trials, a recent survey found that most cat owners were unsure about whether they would consider enrolling their cat in a hypothetical trial, though 71% of owners who had previously participated in a clinical trial would consider participating again. Important factors in owners’ decisions included the recommendation of their primary veterinarian, the number of visits, and the risk of discomfort to their cat [ 19 ]. Although there are barriers to clinical trials in cats, there are opportunities at every level to improve recruitment including education of the public about the importance of routine veterinary care and the existence of clinical trials, of primary care veterinarians about clinical trial opportunities and of both primary care and specialist veterinarians about ‘feline-friendly’ or low-stress handling techniques.…”
Section: Introductionmentioning
confidence: 99%
“…A parallel design study with only one treatment period per cat would likely relieve this impediment. In general, a high number of trips has been reported to decrease owner willingness to participate in clinical studies ( 21 ).…”
Section: Discussionmentioning
confidence: 99%